MANEJO DA SÍNDROME CORONARIANA AGUDA: DA TERAPIA FARMACOLÓGICA À INTERVENÇÃO CORONÁRIA PERCUTÂNEA - Martins Fernandez, João Henrique; MORAES DIAS, VANESSA; Anzolin Alves, Gustavo; Sempio Faria Figueiredo Costa, Isabella; Souza Medrano da Rosa, Rômulo; Borges de Oliveira, Alexandra; Borges de Oliveira, Gabriella; Curvo Bett, Gabriel; Bicalho de Alencar Minuzzi Capeletti, Theodoro Augusto; Zardini Dourado Cunha Ribeiro, ⁠Jéssika; Ribeiro Da Silva, Thiago Matheus; Medeiros, Iasmim (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Acute Coronary Syndrome (ACS) is a cardiovascular emergency characterized by the instability of the atherosclerotic plaque and subsequent abrupt reduction in coronary blood flow, leading to myocardial ischemia. The management of ACS has evolved significantly in recent decades, incorporating pharmacological approaches and percutaneous interventions to improve clinical outcomes. This review seeks to discuss the main therapeutic strategies, from pharmacological therapy to percutaneous coronary intervention (PCI), evaluating the evidence that supports each modality. Methodology: A comprehensive search was carried out in the PubMed, Scopus and Embase databases, using the descriptors "Acute Coronary Syndrome", "Pharmacological Therapy" and "Percutaneous Coronary Intervention". Randomized studies, systematic reviews and guidelines published in the last 10 years were included. The articles were selected based on their clinical and methodological relevance, addressing both the initial management and definitive treatment of ACS. Discussion: Initial management of ACS is focused on stabilizing the patient and preventing additional ischemic events. Dual antiplatelet therapy (DAPT), with aspirin and P2Y12 receptor inhibitors, such as clopidogrel, ticagrelor or prasugrel, is the basis of pharmacological treatment, demonstrating a significant reduction in mortality and thrombotic complications. Anticoagulants, such as heparin or enoxaparin, are also widely used to prevent thrombus formation. Percutaneous coronary intervention (PCI) is indicated for patients with ST-segment elevation myocardial infarction (STEMI) and for those with high-risk non-ST-elevation myocardial infarction (STEMI), aiming to revascularize the occluded artery. Studies such as TRITON-TIMI 38 and PLATO highlight the importance of PCI associated with pharmacological therapy to reduce adverse outcomes. Furthermore, early revascularization is effective in reducing long-term mortality compared to conservative therapy. Conclusion: Managing Acute Coronary Syndrome requires an integrated approach combining pharmacological strategies and invasive interventions, such as PCI, to optimize clinical results. Dual antiplatelet therapy and the use of anticoagulants are fundamental for the initial control of the disease, while percutaneous coronary intervention plays a crucial role in the revascularization of high-risk patients. The continued development of PCI therapies and techniques has the potential to further improve outcomes in patients with ACS.